MASYARAKAT PEMUJA GUNUNG SANGAKU SHINKO: Kepercayaan terhadap Gunung bagi Masyarakat Jepang - Fajria Noviana (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2008)
Mountains play some important parts in the spiritual life of Japanese society, especially for those who live in mountains and their surroundings. Since Ancient Japan Era, mountains have come to people’s object of worship, not only in Japan but also in the world. There are lots of facts showing the existence of mountain worship conducted by a certain society. Mountain worship has become a part of some Japanese life which until now still remains in the form of person-to-person worship, as well as in religious institutions. This mountain worship phenomenon conducted by Japanese society generates problems concerning mountains for most Japanese.